Membangun Dasar yang Kuat: Pelaksanaan dan Tantangan Asesmen pada Fase Fondasi: Building a Strong Foundation: Implementation and Challenges of Assesment in the Foundation Phase - Ima Cahyani Syafitri; Mardiyana Faridhatul Anawaty; Titin Faridatun Nisa' (Universitas Ngudi Waluyo, 2025)
Assessment in the independent curriculum frees each institution to plan and design assessment instruments that are appropriate to the stages of child development and the needs of each school. The purpose of this study was to analyze assessment practices and obstacles faced by teachers. This type of research uses a qualitative research method that refers to the phenomenological paradigm. This research was conducted at the YKK 01 Kindergarten institution in Bangkalan Regency involving the principal and teachers in August-December 2024. Data collection techniques were by interview, participant observation and documentation. The data analysis technique used the Miles and Huberman model, namely data collection, data reduction, data display, conclusion drawing and data verification. The results of the study regarding the implementation and challenges of the foundation phase learning assessment were that teachers used checklists and work results in implementing the assessment and at certain times used anecdotal notes instruments. The challenges faced by teachers, first, the different characteristics of children so that they affect the assessment results, second, communicating the assessment results to align teacher perceptions with parents. This research recommends that teachers can increase the duration of use of assessment instruments other than checklists and work results that are tailored to children's needs and can increase the use of technology to collect, store, and analyze assessment data so as to help monitor children's development more efficiently and facilitate communication with parents. ABSTRAK Asesmen pada kurikulum merdeka membebaskan setiap lembaga untuk merencanakan dan merancang instrumen asesmen yang sesuai dengan tahapan perkembangan anak dan kebutuhan masing-masing sekolah. Tujuan penelitian ini untuk menganalisis praktik asesmen dan kendala yang guru hadapi. Jenis penelitian ini menggunakan metode penelitian kualitatif yang merujuk pada paradigma fenomenologi. Penelitian ini dilaksanakan pada lembaga TK YKK 01 Kabupaten Bangkalan yang melibatkan kepala sekolah dan guru pada bulan Agustus-Desember 2024. Teknik pengumpulan data dengan cara wawancara, observasi partisipasi dan dokumentasi. Teknik analisis data menggunakan model Miles and Huberman yaitu pengumpulan data (data collection), reduksi data (data reduction), penyajian data (data display), penarikan kesimpulan dan verifikasi data (conclusion drawing and verification). Hasil dari penelitian mengenai pelaksanaan dan tantangan asesmen pembelajaran fase fondasi yaitu guru menggunakan ceklis dan hasil karya dalam pelaksanaan asesmen dan pada waktu tertentu menggunakan instrument catatan anekdot. Tantangan yang dihadapi oleh guru, pertama, karakteristik anak yang berbeda-beda sehingga berpengaruh terhadap hasil asemen, kedua, mengkomunikasikan hasil assesmen untuk menyelaraskan presepsi guru dengan orangtua. Rekomendasi penelitian ini, guru dapat meningkatkan durasi penggunaan instrument asesmen selain ceklis dan hasil karya yang disesuaikan dengan kebutuhan anak dan dapat meningkatkan penggunaan teknologi untuk mengumpulkan, menyimpan, dan menganalisis data asesmen sehingga membantu dalam memantau perkembangan anak secara lebih efisien dan memudahkan komunikasi dengan orangtua.